2017
DOI: 10.1007/s00464-017-5530-0
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy compared with pneumatic dilation for newly diagnosed achalasia

Abstract: In the intermediate term, the remission rate of symptoms associated with POEM therapy was better than that with PD for newly diagnosed achalasia, especially in patients with type III achalasia. The short-term outcomes of the two therapies were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Hence, the 40-mm Rigiflex dilator was not used in our study, which was performed in the Asian countries. [22][23][24] In this study, because of the small sample size, no statistically significant difference was observed between the two therapies in the multivariate analysis of symptom return in types II and III achalasia. However, in multivariate analysis, POEM tended to show better outcomes than BD in type III achalasia (HR 11.88, P = 0.082; the difference was not statistically significant because of the small number of patients) rather than in type I (HR 4.69, P = 0.02) or type II (HR 7.08, P = 0.066) achalasia (Table 4).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Hence, the 40-mm Rigiflex dilator was not used in our study, which was performed in the Asian countries. [22][23][24] In this study, because of the small sample size, no statistically significant difference was observed between the two therapies in the multivariate analysis of symptom return in types II and III achalasia. However, in multivariate analysis, POEM tended to show better outcomes than BD in type III achalasia (HR 11.88, P = 0.082; the difference was not statistically significant because of the small number of patients) rather than in type I (HR 4.69, P = 0.02) or type II (HR 7.08, P = 0.066) achalasia (Table 4).…”
Section: Discussionmentioning
confidence: 59%
“…And we did not use a 40‐mm balloon, and as for most Asian patients, 30‐ or 35‐mm‐diameter dilators are the most appropriate. Hence, the 40‐mm Rigiflex dilator was not used in our study, which was performed in the Asian countries …”
Section: Discussionmentioning
confidence: 99%
“…Twenty articles were included in the review (1575 patients) ( Fig . ). Three studies reported data on botulinum toxin (58 patients), 11 on pneumatic dilatation (485 patients), nine on LHM (583 patients) and seven on POEM (449 patients) ( Tables and ).…”
Section: Resultsmentioning
confidence: 99%
“…A score from 0 to 3 was given to each symptom and a total score of 3 or less defined success. The remaining studies used the Eckardt score, and a score of 3 or less was used to define clinical remission.…”
Section: Resultsmentioning
confidence: 99%
“…Current evidence suggests little diff erence in effi cacy between PD, laparoscopic Heller myotomy, or per-oral endoscopic myotomy (POEM) for managing achalasia as measured by patient-reported outcomes ( 13,14 ), but PD oft en requires sequential treatments with progressively larger dilators (30, 35, and 40 mm) to achieve that equivalent effi cacy. Current practice is to begin conservatively with a 30 mm dilation and to determine the need for subsequent dilations based on clinical response as assessed aft er a relatively brief follow-up interval.…”
mentioning
confidence: 99%